2019
DOI: 10.1002/anie.201901525
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Imaging of Nanoparticle Transport in the Kidneys at High Temporal Resolution

Abstract: Noninvasive monitoring of kidney elimination of engineered nanoparticles at high temporal and spatial resolution will not only significantly advance our fundamental understandings of nephrology on the nanoscale, but also aid in the early detection of kidney disease, which affects more than 10 % of the worldwide population. Taking advantage of strong NIR absorption of the well‐defined Au25(SG)18 nanocluster, photoacoustic (PA) imaging was used to visualize its transport in situ through the aorta to the renal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 37 publications
0
47
0
Order By: Relevance
“…However, such gold nanoclusters exhibit always‐on PA signals and the signal difference relies on the different accumulation in the obstructed kidney due to decreased glomerular filtration rate (GFR). [ 28 ] Therefore, development of activatable PA probes for real‐time detection and diagnosis of kidney injury remains challenging.…”
Section: Figurementioning
confidence: 99%
“…However, such gold nanoclusters exhibit always‐on PA signals and the signal difference relies on the different accumulation in the obstructed kidney due to decreased glomerular filtration rate (GFR). [ 28 ] Therefore, development of activatable PA probes for real‐time detection and diagnosis of kidney injury remains challenging.…”
Section: Figurementioning
confidence: 99%
“…GS-AuNP PA allows to take a clear image every second and, therefore, to visualize NPs transportation in real-time from the aorta to the renal parenchyma, their renal filtration, and their elimination. The data collected can then be used to quantify the GFR in healthy and unilateral ureteral obstruction (UUO) kidneys, demonstrating the possibility of applying this technology to detect the early stage of kidney injury [40].…”
Section: Optical Imagingmentioning
confidence: 99%
“…Jiang et al in 2019 reported the strong NIR absorption of Au 25 (SG) 18 nanoclusters and successfully used these for photoacoustic (PA) imaging to in situ visualize their transport through the aorta to the renal parenchyma and subsequent filtration into the renal pelvis at a temporal resolution down to 1 s. [ 101 ] Ultrasmall gold nanoclusters (Au NCs) with a particle size of ~1 nm are emerging as promising nanoparticles due to their structure, unique physicochemical properties, facile surface functionalization, and good biocompatibility [ 102 ] ; they have many unique advantages and exhibit great potential in biomedical research. [ 103 ]…”
Section: Applicationmentioning
confidence: 99%